(untitled) (Research, Society and Development, 2022)
The postpartum period corresponds to the period between the expulsion of the fetus and ends of the phenomena generated by pregnancy ceases. Some complications are independent of the mode of delivery, among the main findings is sexual dysfunction, exemplified mainly by the decrease in sexual desire and, consequently, a decrease in the woman’s quality of life. The objective of the present study was to analyze the main factors related to female sexual dysfunctions during the postpartum period. This is a systematic review using the PRISMA protocol. Therefore, the strategy used in this study included carrying out systematic searches in the literature, using PubMed, Lilacs, Scielo and PEDro databases. For analysis, 16 articles were included in the research. It is concluded that the main causes of sexual dysfunctions were anxiety and depression, especially in the immediate postpartum period, where there was a need for understanding from the partner for the resumption of sexual activities. The literature does not present a consensus on which mode of delivery suggests more sexual dysfunctions, but the history of obstetric pelvic injury hinders the return of sexual activities, generating more pain and fatigue during intercourse. In turn, the cesarean delivery method decreased vaginal lubrication and sexual satisfaction in the women studied.